Answer:
4x-3 is the inverse of given function.
Explanation:
Given function is
f(x) = x+3 / 4
Putting y = f(x) in above equation, we have
y = x+3 / 4
We have to separate x from above equation.
Multiplying 4 by above equation, we have
4y = 4(x+3 / 4)
4y = x+3
Adding -3 to both sides of above equation, we have
4y-3 = x+3-3
4y-3 = x
Swapping above equation, we have
x = 4y-3
Putting x = f⁻¹(y) in above equation , we have
f⁻¹(y) = 4y-3
Replacing y with x in above equation, we have
f⁻¹(x) = 4x-3 which is the answer.